خصوصية إلغاء القرارات الإدارية المشوبة بعيب الانحراف بالسلطة - بولقواس, سناء (revue mofakir, 2018)
Generally, every issued administrative decision should be aimed to realize the public interest, as it must achieve the legislature desired goal, to go with it and to avoid deviations or it would be defected by the power deviation uses. Here comes the importance of the judicial control, particularly, over the administration work, to protect individual’s rights and their freedoms from the deviation use of the administration authorities offered by the law, viewing the particularity given to the deviation authority as a hidden defect, the cancellation of the defected decision is characterized by a special particularity.